2010
DOI: 10.1107/s0108768109053257
|View full text |Cite
|
Sign up to set email alerts
|

Structures of dipeptides: the head-to-tail story

Abstract: The hydrogen-bonding patterns in crystal structures of unprotected, zwitterionic dipeptides are dominated by head-to-tail chains involving the N-terminal amino groups and the C-terminal carboxylate groups. Patterns that include two concomitant chains, thus generating a hydrogen-bonded layer, are of special interest. A comprehensive survey shows that dipeptide structures can conveniently be divided into only four distinct patterns, differing by definition in the symmetry of the head-to-tail chains and amide hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Structural studies that were conducted by Gorbitz [21][22][23] revealed that the FF-PNT has hexagon P 6 1 space group symmetry and this was later confirmed by other studies [26]. The X-ray analysis [13] showed that the temperature-driven process is changing the initial space hexagonal symmetry P 6 1 of hollow native FF-PNT to orthorhombic D 2 h of heat treated closed-end FF-PNF.…”
Section: Temperature-induced Phase Transition and Physical Propertiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Structural studies that were conducted by Gorbitz [21][22][23] revealed that the FF-PNT has hexagon P 6 1 space group symmetry and this was later confirmed by other studies [26]. The X-ray analysis [13] showed that the temperature-driven process is changing the initial space hexagonal symmetry P 6 1 of hollow native FF-PNT to orthorhombic D 2 h of heat treated closed-end FF-PNF.…”
Section: Temperature-induced Phase Transition and Physical Propertiesmentioning
confidence: 83%
“…Such a classification allows observing diverse ferroelectric and related phenomena, which are described by tensors of the odd rank, such as piezoelectric, linear electro-optical, nonlinear optical effects, etc. Some of the dipeptide structures [21][22][23] considered by Gorbitz possess crystalline symmetries that related to pyroelectric classes, meaning a direct evidence of the existence of spontaneous electrical polarization. In this context, peptide molecular dipole engineering is intensively developed in the last years by Kimura [24].…”
Section: Biological Protein Fibers and Bioinspired Peptide Supramolecmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphate moiety in phosphoseryl residue 1 acts as a single proton donor (O10-H10ÁÁÁO1W), but six times as a proton acceptor, while the corresponding group in phosphoseryl residue 2 is a proton acceptor five times and a donor once (O20-H20AÁÁÁO3W/O3A), if the disorder of O3W/O3A is considered. It should be noted that no head-to-tail chains, which are characteristic in common peptide aggregation [3,4], can be found in the aggregation of glycyl-L-glutamyl-L-phosphoseryl-L-leucine. Instead the hydrogen bonds connect the N-terminal amino group to the phosphate groups of the peptide.…”
Section: Resultsmentioning
confidence: 99%
“…For the first time, the analysis of the supermolecu lar PT structure formed from different peptides was performed in [16][17][18] (a total of 160 different peptides were analyzed). It was shown that an overwhelming majority of considered structures consist of separate crystalline substructures without a center of inversion.…”
Section: Introductionmentioning
confidence: 99%